Elton John and Tim Rice's Aida - John, Elton 1947- (Rocket Records, 1999)
This compact disc includes songs that were written by Elton John and Tim Rice for an original musical for Disney. The songs included here are merely a selection of songs written for the musical and are not identical to the ones that will be used on stage
Lyrics in insert in container ; liner notes by Tim Rice
Keywords: Musicals; Musicals / Librettos; CD